Variation in urine output from shelter cats is explained by shelter location, not kennel size - Allison Andrukonis; Nathaniel J. Hall (PLoS ONE, 2025)
Monitoring and decreasing stress in cats housed in animal shelters is essential for maintaining adequate welfare. Urine output is a potential indicator of shelter cat stress. The present study aimed to evaluate the impact of the provision of extra space using a portal connecting two kennels and daily petting on urine output at two different municipal shelters in the United States. Cats (n =  59) were randomly assigned to one of four groups: Control, Portal, Petting, and Portal and Petting. Litter clumps were weighed daily for five days as a measure of urine output. Additionally, cats were given a daily Cat Stress Score. Experimental group did not significantly predict urine output nor Cat Stress Score. However, living at Shelter B significantly predicted increased urine output. The results from the present study suggest that shelter-related factors might impact urine output of cats more than kennel size or petting alone.